Post-COVID-19 Trends in Elementary Science Education: Dominant Methods, Media, and Assessment Practices - Azis, Donny Khoirul; Sarah, Siti; Febriana, Maghfira; Rohmad, Rohmad; Fajaruddin, Syarief; Irambona, Alfred (Jurnal Prima Edukasia, 2024)
This study aims to determine the trend of elementary/MI science learning in the post-COVID- 19 pandemic era. The research used a survey design. Data collection methods included observation, interviews, and documentation. All instruments were tested for content validity and construct validity. Data triangulation was done by comparing and checking data obtained from information from parties who played a role in the research. After that, data analysis was carried out. Data analysis techniques used qualitative descriptive and quantitative descriptive analysis techniques. The study concluded that the post-COVID-19 SD/MI science learning trends lead to the following indicators including (1) the dominant learning method is lecture, (2) blackboards and markers are the dominant learning media, (3) student worksheets (LKS) are learning resources that are highly used by teachers, (4) assessment instruments used files/paper/written (5) oral tests are an assessment technique that is highly used by teachers, (6) cognitive assessment is the teachers' favorite in evaluations, (7) the realm of cognitive assessment in the majority is still oriented towards LOTS (Low Order Thinking Skills), namely understanding and remembering, and (8) aspects of discipline and responsibility are the main affective assessments that most teachers do. These findings imply that there is a need for more diverse and higher- order thinking skills (HOTS)-oriented teaching and assessment methods to enhance the overall quality of science education.